Determinant of purchasing behavior of medicines in neighborhood sundry stores among Filipino households in Manila City: a cross-sectional study - Cañares, Denielle Criscel B.; Ocampo, Patricia Maxine M.; Tabinas, Valerie Juness Anne I.; Gloria, Mac Ardy J. (Manila: Department of Pharmacy, College of Pharmacy, University of the Philippines Manila, 2024)
Introduction: Retail outlets for non-prescription drugs (RONPDS) have improved access to medicines. However, establishments like neighborhood sundry stores (NSS), still illegally sell medicines, posing significant risks to consumers. Notably, there has been limited evidence identifying the determinants of purchasing behavior of medicines in NSS among Filipino households.

Objectives: This study aims to identify the determinants of the purchasing behavior of Filipino households in Manila City regarding prescription and non-prescription medicines in NSS.

Methods: A quantitative, cross-sectional research design was employed, with systematic stratified random sampling conducted in 385 households wherein a 7-part survey was administered. We analyzed the data using descriptive statistics and multiple linear and logistic regression analysis.

Results: Most were aged 30-39 (40.78%), female (60.26%), college-educated (52.73%), employed (61.56%) with a monthly income of Php 21,914-43,828 (27.53%), and had no specific health conditions (80.26%). There were negative attitudes towards medicines in NSS (x̄=3.26), positive subjective norms (x̄=2.68), negative perceived behavioral control (x̄=3.43), and negative purchasing intention (x̄=3.33). Most disagreed with intention to buy medicines in NSS (29.10%) but were neutral on predicting purchases (28.10%) and likelihood to buy (28.80%). Lastly, 85.97% had previously purchased from NSS. Significant determinants of purchasing intention include Perceived Behavioral Control (Coeff 0.49; p<0.01), Subjective Norm (Coeff 0.23; p<0.01), and Attitude (Coeff 0.30; p<0.01), while significant predictors for purchasing behavior are income (Coeff 0.06; p<0.01), subjective norms (Coeff 0.536; p<0.03), and perceived behavioral control (Coeff 0.61; p<0.01).

Conclusions: Many Filipino consumers risk buying counterfeit/adulterated medicines by patronizing NSS. Strengthened regulations, better policies, and targeted campaigns are recommended to increase awareness and improve purchasing practices.
Thesis (Bachelor of Science in Pharmacy)--University of the Philippines Manila, June 2024
Keywords: Consumer behavior -- Manila. -- Philippines; Pharmaceutical industry -- Purchasing -- Manila. -- Philippines; Community Pharmacy Services. -- Manila. -- Philippines .; Drugstores -- Manila. -- Philippines; Cross-sectional studies